Pengaruh Kualitas Produk, Harga, dan Pelayanan Terhadap Keputusan Pembelian Konsumen di Toko UNA Parfum - Abdullah Thufail Fikri; Mohammad Ali; Cucu Hayati (PUTRA JAWA PUBLISHER, 2025)
This study aims to analyze the effect of product quality, price, and service on consumer purchasing decisions at Una Perfume Store. The background of this research is the increasingly intense competition in the perfume business, which requires a deeper understanding of the factors that influence consumers in making purchasing decisions.This research employs a quantitative approach with a survey method. The population consists of all consumers of Una Perfume Store, while the sample comprises 50 respondents selected using the Slovin formula. Data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS version 23.0.The results indicate that both partially and simultaneously, product quality, price, and service have a significant effect on consumer purchasing decisions. Superior product quality, competitive pricing, and satisfactory service have been proven to increase consumer purchase intention. Among these three variables, product quality has the most dominant influence on purchasing decisions.This study concludes that Una Perfume Store should maintain product quality, implement an appropriate pricing strategy, and continuously improve service quality to retain loyal customers and attract new ones. The findings of this research are expected to serve as a reference for perfume business owners in designing effective marketing strategies.